2011
DOI: 10.1186/1475-2875-10-387
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomized study of intermittent preventive treatment for malaria in infants (IPTi) in southern Tanzania: evaluation of impact on survival

Abstract: BackgroundIntermittent Preventive Treatment for malaria control in infants (IPTi) consists of the administration of a treatment dose of an anti-malarial drug, usually sulphadoxine-pyrimethamine, at scheduled intervals, regardless of the presence of Plasmodium falciparum infection. A pooled analysis of individually randomized trials reported that IPTi reduced clinical episodes by 30%. This study evaluated the effect of IPTi on child survival in the context of a five-district implementation project in southern T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Baseline neonatal mortality and newborn care practices were assessed through a survey of all households in five of the six study districts in 2007 (excluding Mtwara Rural) as part of a study assessing the effect of intermittent preventive treatment of malaria in infants [ 18 , 27 ]. In 2013 we did a representative household survey, including 185,000 households from all 132 wards.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline neonatal mortality and newborn care practices were assessed through a survey of all households in five of the six study districts in 2007 (excluding Mtwara Rural) as part of a study assessing the effect of intermittent preventive treatment of malaria in infants [ 18 , 27 ]. In 2013 we did a representative household survey, including 185,000 households from all 132 wards.…”
Section: Methodsmentioning
confidence: 99%
“…The results from an evaluation of implementing IPTi in five districts in Southern Tanzania showed no effects on child survival attributable to the intervention (Schellenberg et al 2011). Translating evidence into practice depends on systems and situations that are different from trial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Translating evidence into practice depends on systems and situations that are different from trial conditions. As Schellenberg et al say (2011), there are ‘real-life’ challenges in health systems (e.g. low coverage, late administration) that can act as significant constrain to the replication of trial results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-ana lysis of six trials of IPTi using SP, the intervention decreased malaria episodes by 30%, anemia by 21%, malaria hospital admissions by 38% and overall hospital admissions by 23% [121]. However, a randomized clinical trial of IPTi using mortality as an outcome showed no benefit [122]. The WHO conditionally recommends IPTi for children in moderate-tohigh transmission areas where resistance to SP is less than 50% [123].…”
Section: Prevention Strategiesmentioning
confidence: 99%